Identification, function validation and haplotype analysis of salt-tolerant genes of lectin receptor kinase gene family in sorghum (Sorghum bicolor L.) - Mao, Li; Huazhuan, He; Haiyan, Gao; Wangqi, Huang; Qizhe, Cai; Guiyun, Yan; Qingjun, Cheng; Yinpei, Liang; Xiuhua, Chen (Frontiers in Genetics, 2024)
Salt stress is one of the significant challenges in sorghum production, which greatly impact the yield of sorghum. L-type lectin receptor kinases (LLRLK) are essential for plant stress tolerance, yet a comprehensive genome-level analysis in Sorghum bicolor has not been conducted. This study identified 49 SbLLRLK genes in S. bicolor, categorized into four groups based on their lectin domain characteristics. The gene structures and motifs were found to be relatively conserved among these SbLLRLK genes. Diverse expression patterns of SbLLRLK genes were observed under various stress conditions, including salt, drought, and heat. Furthermore, through homologous gene alignment and transgenic analysis, SORBI_3004G304700 was identified as a gene that negatively regulates plant salt stress tolerance. Haplotype analysis of SORBI_3004G304700 revealed three unique haplotypes, with haplotype1 being the most prevalent, possibly due to selective advantages for salt stress tolerance. These findings offer valuable insights for biological research and present a potential candidate gene for future genetic enhancement of sorghum.